RESEPSI SANTRI DAN GENEOLOGI TRADISI WIRID FAFAHAMNA: Kajian Living Qur’an di Pondok Pesantren Al-Fattah Kartasura - Muhamad Khabib Imdad; Fiqih Firdaus (AL ITQAN: Jurnal Studi Al-Qur'an, 2023)
There are many traditions in Islamic societies or groups that originate from the existence of the Quran in their midst. As recently, various traditions of reading the text of the Koran have become widespread, both carried out communally and individually. Normally reading the Quran can be done at any time, but a tradition has emerged so that the Quran or parts of it can only be read at certain times. This phenomenon also applies to the Al-Fattah Kartasura Islamic Boarding School which has a tradition of reading the wirid fafahamna or Al-Anbiya' verse 79 after Isha' prayer communally by the students. This then led the author to trace the genealogy of this tradition and explore how the students received it. This research is qualitative research with a field research approach to this traditional phenomenon. The data source for this research was obtained from information from several elements of Islamic boarding schools, namely caregivers, administrators and students. The data collection techniques use interviews, observation and documentation. Meanwhile, checking the validity of the data uses the data triangulation method with techniques and sources with research methods applying descriptive-analytical methods. The results of this research are, Genealogically, this remembrance was obtained by the caretaker from Fathurrahman who came from Kyai Idris Kacangan Boyolali, His tradition has spawned several receptions from students, namely forming personality, bringing peace of mind, making all matters easier, and making learning easier.